Stewards for future: Piloting a medical undergraduate elective on antimicrobial stewardship - Papan, Cihan; Gärtner, Barbara C.; Simon, Arne; Müller, Rachel; Fischer, Martin R.; Darici, Dogus; Becker, Sören L.; Last, Katharina; Bushuven, Stefan (GMS Journal for Medical Education)
Background: The rise of antimicrobial resistance as leading infection-related cause of death will necessitate trans-sectoral efforts on a global level. While many antimicrobial stewardship (AMS) incentives target healthcare workers, addressing undergraduates offers new and hitherto neglected opportunities. Methods: We describe the pilot phase of a novel undergraduate elective (“stewards for future”, SFF) for medical students at the Saarland University, Germany, between 2021 and 2023. We focused on knowledge and attitudes relevant to AMS. To allow for full immersion, we applied case-based learning, problem-based learning, and peer teaching in a small group teaching format spanning 15 hours, including AMS ward rounds. We obtained students’ pre- and post-course self-assessment regarding AMS topics using 5-point Likert scales modified from the previously published ASSURE elective, as well as their subjective experience using the German short intrinsic motivation inventory. Results: Over four terms, 23 undergraduate medical students from the clinical phase participated in the elective. Participants reported an increase in their ability to explain the concept of AMS (mean and standard deviation, pre 3.26±0.94 vs. post 4.74±0.44, p<0.0001), their confidence in choosing the appropriate antibiotic (pre 2.22±0.78 vs. post 3.57±0.58, p<0.0001), their ability to judge potential drug side effects (pre 2.09±0.72 vs. post 3.43±0.71, p<0.0001), their confidence in communicating with colleagues about antibiotics (pre 2.30±0.86 vs. post 3.52±0.83, p<0.0001), their understanding of diagnostics as an AMS tool (pre 4.22±0.41 vs. post 4.91±0.28, p<0.0001), and their ability to evaluate the roles of all AMS team members including their own (pre 2.52±0.77 vs. post 4.13±0.68, p<0.0001). Participants reported having enjoyed the course (4.6±0.5), while they were moderately satisfied with their performance (3.8±1.0). Pressure and anxiety levels were reported to be low (1.8±0.9 and 2.0±1.0 each). Conclusions: Student participants of the elective SFF reported increased competencies relevant to AMS, while enjoying the course format. Sustainability and scalability will ultimately depend on the implementation into the core curriculum.